Deubiquitylation and stabilization of ARMC5 by ubiquitin‐specific processing protease 7 (USP7) are critical for RCC proliferation. Issue 6 (5th February 2021) - Yan, Guobei; Liu, Na; Tian, Jun; Fu, Yanli; Wei, Wei; Zou, Jingjing; Li, Suping; Wang, Qing; Li, Kai; Wang, Junhua
Abstract: The ubiquitin‐proteasome system is an essential regulator of ARMC5, which serves as a new tumour suppressor protein for inhibiting meningiomas and hereditary adrenocortical tumorigenesis. However, the precise mechanism for the deubiquitination of ARMC5 is still not fully understood. A Western blot analysis of ARMC5 was performed and showed that the expression of ARMC5 was decreased in the renal cancer cell tissues and lines. By screening a deubiquitinase library, we identified USP7 as a potential ARMC5 associated deubiquitinase. In this paper, we demonstrated that there was an interaction between USP7 and ARMC5 in vivo and in vitro. Employing the overexpression and knockdown assay indicated that USP7 could greatly increase the steady state of ARMC5 through the ubiquitin‐proteasome pathway and regulate ARMC5 ubiquitination. Moreover, USP7 altered cell cycle G1/S phases and regulated renal cancer cell proliferation by targeting ARMC5. Together, these results suggest that USP7 plays an important role in the RCC proliferation through modulating ARMC5 stability.